Problematics Evaluation of Islamic Education Learning During Covid-19 Pandemic in MTs. Usman Syarif Medan - Tamrin, Muhammad; Enita, Putri; Marpaung, Muhammad Abdurrahman Fauzi; Harahap, Rediani (Sekolah Tinggi Agam Islam Sumatera Medan, 2020)
The goal of this research is to analyze: (1) problems in evaluating Islamic education learning, (2) The impact of the problems, and (3) Solutions for the existing the problems. The research has been done at MTs. Usman Syarif Medan. This research is using descriptive qualitative analysis method. The data collected comes from interviews and some observation. To ensure the validity of the data, the test is carried out by credibility/trust test, transferability test, dependability test and confirmability test. The results of this learning evaluation problem are including: Difficulty of evaluating learning in the cognitive, affective, and psychomotor domains when learning is doing online (in a network). The impact of learning from home has a negative impact on educators and students. The solution to learning problems is to evaluate learning using the WhatsApp application by doing written tests, oral tests, and also quizzes. This solution is a response to learning problems during the Covid-19 pandemic.